Normal and Abnormal Scrotum - Fahmy, Mohamed A. Baky.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is an academic and practical guide to the diagnostic methods and management strategies for both common and rare scrotal diseases. Chapters focus on the normal anthropometric measures of the scrotum as a unique organ and the latest relevant advancements in the field. Techniques including scrotal reconstruction for congenital abnormalities, trauma, and cancer-related extirpation are all covered. Critical tools and methods related to aesthetics are also detailed. Emphasis is also placed on identifying common pitfalls and how to avoid them, ensuring that the reader is fully equipped to deal with a range of scenarios. Normal and Abnormal Scrotum describes how to approach diagnosing and managing the entire range of scrotal diseases, making it essential for all general practitioners, pediatricians, urologists, and pediatric and aesthetic surgeons who encounter these patients in their day-to-day practice.
Introduction -- Nomenclature and terminology -- Scrotum in Human Conscience -- Scrotal Evolution -- Animal Scrota -- Scrotal Functions and Missions -- Embryology of Scrotum -- Anatomy of Scrotum -- Morphology and Anthropometric Measurements of Scrotum -- Congenital Scrotal Anomalies -- Common anomalies -- Rare anomalies -- Scrotomegaly -- Vascular anomalies -- Scrotal calcinosis -- Case reports -- Common acquired diseases of scrotum -- Acute scrotum -- Rare acquired diseases of scrotum -- Neoplastic lesions of scrotum -- Scrotal swelling and cysts -- Dermatological diseases specific to scrotum -- Scrotal Imaging -- Scrotoplasty.
Keywords: Urology; Genitourinary organs$1 (BSurgery.s; Pediatrics; Urology; Urological Surgery; Pediatrics; Scrotum -- abnormalities; Scrotum -- anatomy & histology